(( تأثير تمارين التنفس المنتظمة على مستوى الألم أثناء تركيب القثطرة الوريدية عند الأطفال في سن المدرسة )) - دونا عيسى; جوني عدي; المحمد عبد الله محمد (Latakia University Journal -Medical Sciences Series, 2014)
يعتقد بعض الباحثين في مجال الألم بأن هناك علاقة بين التحكم بالتنفس ومستوى الألم ولاسيما أثناء تلقي تنبيهٍ أو إجراءٍ مؤلم , إذ تزيد تمارين التنفس السعة التنفسية وبالتالي تساعد على زيادة مستوى الأكسجة الدموية وتطرح ثاني أوكسيد الكربون , وتساعد على تحقيق درجة مناسبة من الاسترخاء , والذي يقلل نقل السيالات العصبية التي تنقل إحساسات الألم من أماكن الألم , يهدف البحث إلى دراسة تأثير تمارين التنفس العميق المنتظم على مستوى الألم أثناء تركيب القثطرة الوريدية عند الأطفال في سن المدرسة , أجري هذا البحث على عينة قوامها 60 طفلاً بعمر بين 6 -12 سنة , وأجريت الدراسة في مشفى الأسد الجامعي ومشفى التوليد والأطفال في مدينة اللاذقية وتم تقسيم عينة البحث إلى ضابطة وتجريبية قامت المجموعة التجريبية بتطبيق تمارين التنفس العميق قبل وأثناء تركيب القثطرة الوريدية. وكانت أهم نتائج البحث كما يلي ( متوسط درجة الألم عند الأطفال من المجموعة التجريبية 1.075 بينما متوسط درجة الألم عند الأطفال من المجموعة الضابطة 3.45 وذلك وفقاً لمقياسFacial Expression Scale ), وكانت أهم الاستنتاجات لهذه الدراسة أنه كان لتمارين التنفس العميق المنتظم دوراً بارزاً في تقليل درجة الألم أثناء تركيب القثطرة الوريدية عند الأطفال في سن المدرسة . Some researchers in the field of pain think that there is a relationship between breathing control and level of pain, especially during painful procedures. Breathing exercises increase breathing capacity and that can help increase blood oxygenation level and exhalation of co2, and help in relaxation. It can also decrease nervous single transmission that transmits pain sensations from pain sites. This research aims to study the effect of regular breathing exercises on level of pain during intravenous catheterization in children of school age. The sample of study was 60 children between (6-12) years. The study was done in Alasad Hospital and Children’s Hospital in Lattakia. The sample was divided into two groups: (experimental group and control group). The experimental group had implemented deep breathing exercises during intravenous catheterization. The tool of research was Facial Expression Scale and Analoge scale. The most important results of the study were (the average of pain level in experimental group was 1.075 while the average of pain level in control group was 3.45 by Facial exceprission scale). The most important conclusion of the study was that breathing exercises play a big role in decreasing pain during intravenous catheterization in children of school age.